A Novel Biopsy Method Based on Bipolar Radiofrequency Biopsy Needles - Wang, Huiyang; Bao, Haiwei; Yue, Lan; Jiang, Tian’an (Frontiers in Oncology, 2022)
Modern oncology increasingly relies on pathological, molecular, and genomic assessments of biopsied tumor tissue. However, the concern for bleeding complication and malignant seeding severely hinders the application of the biopsy tumor. Here, we developed a 16 G biopsy needle to contain two electrodes insulated from each other and connect to an radiofrequency generator. For evaluating hemostatic efficacy, 50 rabbits were randomly divided into two groups: warfarinization and non-warfarinization group. Two liver biopsies and two splenic biopsies per animal were performed using a 16 G biopsy needle. Each group was further equally divided into five groups according to different hemostatic measures, including non-intervention, embolization using an absorbable gelatin sponge, and ablation by RF with three different needle temperatures (50 °C, 70 °C, and 90 °C). Than, we used VX2 rabbit models (n = 25) and applied the five analogous biopsies to the tumor. The flush fluid from the biopsy needle underwent cytomorphological analysis. Our results that the groups using ablation by RF showed significantly less blood loss than the control group for liver and spleen in both groups (P < 0.001). After RF ablation, thermal coagulation of the tissue surrounding the needle tract was observed on both the macroscopic and histological level. Cytological smears showed that tumor cells were degenerated after RF at 70°C and 90°C. Our findings showed that bipolar RF biopsy needle is a promising tool for reducing hemorrhage after biopsy and avoiding implanting tumor cells in the tract.